Inter-American Memories: Frances Toor, Alma Reed and the Mexican Cultural Renaissance - Michael K. Schuessler (Les Cahiers de Framespa)
This article discusses the lives and cultural projects of Frances Toor and Alma Reed, two US women who traveled to Mexico shortly after the Mexican Revolution (1910-1920). Within the context of post-revolutionary Mexico and the artistic and ideological programs it developed and promoted, these women served as early bicultural bridges linking two countries with a historically fraught political relationship. Alma Reed’s romantic involvement with Felipe Carrillo Puerto and her later activities as a promoter of artist José Clemente Orozco and scholar of pre-Hispanic Mexico are explored within the political backdrop of this foundational moment of Mexico’s modern history. As for Frances Toor, she founded and edited the groundbreaking bilingual magazine Mexican Folkways, which explored and celebrated the artistic traditions of the country’s myriad indigenous groups and, due to its bilingual nature, also served as a vehicle to spread knowledge about Mexico and its rich cultural heritage in the United States and beyond.